2012
DOI: 10.11606/issn.2176-7262.v45i3p337-342
|View full text |Cite
|
Sign up to set email alerts
|

Características clínicas de fumantes atendidos em um centro de referência na cessação do tabagismo

Abstract: Objetivo: Descrever características demográficas e clínicas de fumantes que procuraram atendimentoem centro especializado na cessação de tabagismo. Métodos: Foram analisadas, retrospectivamente,as informações disponíveis em ficha clínica padronizada preenchida no momento do primeiro atendimento, de fumantes que procuraram o Ambulatório de Apoio ao Tabagista do Centro de Saúde Escola daFaculdade de Medicina de Ribeirão Preto da Universidade de São Paulo, no período de 18 meses.Resultados: O serviço foi procurad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0
11

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 2 publications
1
6
0
11
Order By: Relevance
“…However, it is in accordance with the predominantly female characterization (73 %) of an on-demand research, in which the investigated population consisted not only of smokers, but also of smokers seeking help to quit smoking 18 , which is similar to the population analyzed in the current study. The female predominance (70 %) in the group of smokers treated at University Hospital Antônio Pedro (HUAP) had already been identified in a previous study that investigated the Auditory Evoked Potential in smokers 13 .…”
supporting
confidence: 88%
“…However, it is in accordance with the predominantly female characterization (73 %) of an on-demand research, in which the investigated population consisted not only of smokers, but also of smokers seeking help to quit smoking 18 , which is similar to the population analyzed in the current study. The female predominance (70 %) in the group of smokers treated at University Hospital Antônio Pedro (HUAP) had already been identified in a previous study that investigated the Auditory Evoked Potential in smokers 13 .…”
supporting
confidence: 88%
“…26,32 Comparisons between the averages relating to occupation and abandonment of dependence treatment should be viewed with caution. Firstly, the results showed that abandonment occurred more often among those who had an occupation, and this was similar to the findings from other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the results showed that abandonment occurred more often among those who had an occupation, and this was similar to the findings from other studies. 24,26 This issue may be related to the times (morning/afternoon) at This finding shows that the longer the period spent smoking, the more a person will decide to invest in the treatment, perhaps because of the possibility of starting to feel the effects of the diseases caused by tobacco. One of the main reasons why individuals decide to quit smoking relates to the deterioration of health conditions caused by tobacco-related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Talvez ao fumar por pouco tempo, o tabagista ainda não tenha sentido os efeitos nocivos do cigarro à sua saúde e não valorize a importância de parar de fumar, diferentemente dos mais idosos que têm maior preocupação com a sua saúde, fator associado a maior abstinência conforme outras pesquisas. Ou talvez lhe falte maturidade e a consciência de que, independentemente do tempo de fumo, o cigarro pode trazer riscos à sua saúde 35,36 . Por outro lado, a maior carga tabágica mostrou-se associada ao fracasso na cessação.…”
Section: Discussionunclassified